PRICE OF FREEDOM IN FATIMA MERNISSI'S DREAMS OF TRESPASSTALES OF A HAREM GIRLHOOD (1994): A FEMINIST APPROACH - INDRIANI, MIVTA (2011)
The major problem of this study is how the price of freedom reflected in Dreams of Trespass Tales of A Harem Girlhood novel. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on feminist analysis. In analyzing Dreams of Trespass Tales of A Harem Girlhood, the writer uses qualitative method and feminist approach. The data sources consist of primary data and secondary data sources. The primary data source is the novel Dreams of Trespass Tales of A Harem Girlhood itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and feminist. The method of the data collection is descriptive analysis. The outcomes of the study show the following conclusions. First, from the structural elements, it shows that the writer wants to convey her idea of women's freedom. Second, based on feminist approach, Mernissi as the major character wants to have equal treatment with men that is to get the equal position, right, role, and participation.